2016
DOI: 10.1080/11263504.2015.1115438
|View full text |Cite
|
Sign up to set email alerts
|

An updated inventory of the non-native flora of Sardinia (Italy)

Abstract: Aeonium ciliatum (Willd.) Webb & Berthel. C 134 Crass N OP NP Ma v * Aeonium decorum Webb ex Bolle C 134 Crass N C Ch/NP Ma v * Aeschynanthus pulcher (Blume) G.Don C 367 Gesne N OP P AS v * Aesculus hippocastanum L.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…Pampas grass Poaceae several times higher than in other regions (e.g. Ansong et al 2019;Barina et al 2014;Camarda et al 2016;Pysek et al 2012). Nevertheless, there are at least two important caveats when examining such trends.…”
Section: Cortaderia Selloanamentioning
confidence: 98%
“…Pampas grass Poaceae several times higher than in other regions (e.g. Ansong et al 2019;Barina et al 2014;Camarda et al 2016;Pysek et al 2012). Nevertheless, there are at least two important caveats when examining such trends.…”
Section: Cortaderia Selloanamentioning
confidence: 98%
“…1999; Suehs, Médail, and Affre 2001). In Sardinia, Carpobrotus has also naturalized (Camarda et al 2016;EPPO 2006), and in Sicily both C. aff. acinaciformis and C. edulis are reported as frequent on beaches throughout the Island (Giardina, Raimondo, and Spadaro 2007).…”
Section: Introduced Rangementioning
confidence: 99%
“…After a few years, Brundu et al (2003) and Camarda et al (2004) indicated it as naturalized in the island. Later, several authors confirmed the same status (e.g., Podda et al 2011, Camarda et al 2016, Puddu et al 2016 (Galasso et al 2018a). This species has been found in an area previously subjected to weeding of the road margins.…”
Section: Euphorbia Thymifolia L (Euphorbiaceae)mentioning
confidence: 83%
“…It was reported from various localities of southern Sardegna by Bocchieri et al (1982) and Bocchieri (1984), and then confirmed by Arrigoni (2010). Later, Puddu et al (2016) indicated it as a casual alien in Sardegna, while Camarda et al (2016) reported it as naturalized. It is widespread in Gallura, Logudoro, Ogliastra, Sulcis-Iglesiente, Sarrabus-Gerrei and Campidano, from sea level to 1,050 m a.s.l., along roadsides and in fallow land, ruderal places, and gardens, mainly on sandy granitic soils.…”
Section: Floristic Recordsmentioning
confidence: 99%